Síndrome de Burnout y su influencia en el desempeño laboral de los docentes del Décimo Año de Educación Básica del Colegio Beatriz Cueva de Ayora - Procel Rivera, María Belén (2015)
SUMMARY The syndrome of professional depletion or Burnout's syndrome means to be or to feel burnt, exhausted, overloaded, exhausted. This suffering presents three essential components: the emotional depletion, the despersonalization and the lack of professional accomplishment. It usually affects specially teachers, health staff, social workers and in general in those professions that imply a direct interaction with people. The study proposed to determine the presence of the syndrome Burnout and its influence in the labor performance of the teachers of the Tenth Year of Basic Education at the “Beatriz Cueva de Ayora” high school; in addition, to identify by means of Maslach's Test the presence of Burnout's syndrome in the teachers according to the sex, age and years of work; and finally to spread the results obtained to the authorities of the “Beatriz Cueva de Ayora” high school and the delivery of a brochure was done. The type of study was descriptive, using the technique and instrument: Maslach’s standardized test for the teachers and the questionnaire of labor performance applied to the pupils of Tenth Year. It was found that 60 % of teachers suffers from Burnout's syndrome, concerning lightly more to the feminine sex that are in the age bracket older than 50 years and that work as teachers more than 30 years; the presence of Burnout's syndrome is affecting the teaching performance; which is perceived by the students as bad and regular. Finally, the research results were spread to the authorities of the”Beatriz Cueva de Ayora” high school and the brochures was delivered them. The Occupational Health staff of the establishment was suggested to worry about the teachers that suffer the Burnout's syndrome, which is affecting their labor performance; this department can promote educational workshops about prevention and relaxing therapies in order to diminish or even to prevent the spreading of this suffering to other teachers. Key words: Burnout's syndrome, professional depletion, chronic stress, school learning.